N‐terminal diproline and charge group effects on the stabilization of helical conformation in alanine‐based short peptides: CD studies with water and methanol as solvent. (20th April 2017) - Goyal, Bhupesh; Srivastava, Kinshuk Raj; Durani, Susheel
Abstract : Protein folding problem remains a formidable challenge as main chain, side chain and solvent interactions remain entangled and have been difficult to resolve. Alanine‐based short peptides are promising models to dissect protein folding initiation and propagation structurally as well as energetically. The effect of N‐terminal diproline and charged side chains is assessed on the stabilization of helical conformation in alanine‐based short peptides using circular dichroism (CD) with water and methanol as solvent.A1 (Ac–Pro–Pro–Ala–Lys–Ala–Lys–Ala–Lys–Ala–NH2 ) is designed to assess the effect of N‐terminal homochiral diproline and lysine side chains to induce helical conformation.A2 (Ac–Pro–Pro–Glu–Glu–Ala–Ala–Lys–Lys–Ala–NH2 ) andA3 (Ac–d Pro–Pro–Glu–Glu–Ala–Ala–Lys–Lys–Ala–NH2 ) with N‐terminal homochiral and heterochiral diproline, respectively, are designed to assess the effect of Glu...Lys ( i, i + 4) salt bridge interactions on the stabilization of helical conformation. The CD spectra ofA1, A2 andA3 in water manifest different amplitudes of the observed polyproline II (PPII) signals, which indicate different conformational distributions of the polypeptide structure. The strong effect of solvent substitution from water to methanol is observed for the peptides, and CD spectra in methanol evidenceA2 andA3 as helical folds. Temperature‐dependent CD spectra ofA1 andA2 in water depict an isodichroic point reflecting coexistence of two conformations, PPII and β‐strand conformation, which is consistent with the previous studies. The results illuminate the effect of N‐terminal diproline and charged side chains in dictating the preferences for extended‐β, semi‐extended PPII and helical conformation in alanine‐based short peptides. The results of the present study will enhance our understanding on stabilization of helical conformation in short peptides and hence aid in the design of novel peptides with helical structures. Copyright © 2017 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Effect of N‐terminal diproline and charged side chains on the stabilization of helical conformation in alanine‐based nonapeptidesA1, A2 andA3 in water and methanol.